Therapeutic fruit peels: Their role in preventing lifestyle disorders - Chatterjee, Shilpi (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The prevalence and severity of obesity, type 2-diabetes, cardiovascular disease, cancer and respiratory problems are rapidly increasing. As successful preventive and therapeutic strategies for these life-threatening health ailments often come with adverse side effects, nutritional elements have been widely used in many countries as preventive therapies to prevent or manage metabolic syndrome. Fruits are important dietary components and contain various bioactive constituents such as flavonoids, carotenoids and phenols. Evidence suggests that a diet high in fruits and vegetables may decrease the risk of chronic diseases, such as cardiovascular disease and cancer, and phytochemicals including phenolics, flavonoids and carotenoids from fruits and vegetables may play a key role in reducing chronic disease risk. Although various fruits have already been studied worldwide in this connection but the peels of the fruits have mostly remain an underdog. The aim of this article is to review the role of peel of the fruits and their constituents in the regulation of metabolic functions which can beneficially alter the pathophysiology of some of the common as well as chronic ailments. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>